Prognostic factors for early failure of arteriovenous fistulas for hemodialysis - López Chapuis, Daniel; Elters, Antoine; Garrido, Pedro; Prego, Alfredo; Valverdu, Martín (Cirugía del Uruguay, 1993)
The results of 113 angioaccesses far hemodialysis is analysed, evaluating the inciden/ of early failure in its development. 18.5% global failure is found; this rises to 3.3% far humero-cephalic fistulas, 26% far diabetic patients and 22.6% far women. The author comes to the conclusion that diabetes and female are two factors that determina te a worse prognosis in the early development of the vascular access.